Ethnobotanical knowledge of Prunus africana (Hook. f.) Kalkman (Rosaceae) by people living in community forests in North Kivu, Eastern Democratic Republic of Congo - Muhesi, Eloge Kambale; Betti, Jean Lagarde; Din, Ndongo; Kapiri, Moïse Musubao; Afiong, Harmelle Natacha Nana; Fils, Pascal Billong (Ethnobotany Research and Applications, 2023)
Background: Prunus africana (Hook. f) Kalkman (Rosaceae) is a multi-purpose species with important utility value for the populations that depend on it. Indeed, local populations living in community forests use P. africana. The objective of this study is to document the different uses of P. africana by local populations in traditional medicine for a better vulgarization for a sustainable management of the resource. Methods: Ethnobotanical surveys were conducted in four P. africana distribution areas in North Kivu. Data were collected on the basis of a survey from 221 informants. Statistical analysis and calculation of ethnobotanical indices were performed using R 4.1.2 software. Results: Results of the investigations show that P. africana is by far used in medical practices (96.83%). It is also used as wood energy (60.18 %), charcoal (40.27 %), in handicrafts (7.24 %), construction (6.79 %), food (2.26 %) and traditional rites (0.45 %). In traditional pharmacopoeia, the characterization of the uses allowed us to identify 23 diseases for which P. africana extracts are used to treat them. The bark and leaves are the most used organs in the recipes. The decoction (99.5%), the macerated (10.41%) and the powders (7.69%) are the galenic or pharmaceutical forms in which the local populations prepare the remedies. The potions prepared are mainly administered orally (99.5%). Conclusion: The multiple forms of use of P. africana by the populations of North Kivu, both in medicine and in other categories of use, constitute a threat to its survival. For a sustainable management, the results of this study reveal that it is possible to substitute the species P. africana with other plant species with similar potential in order to limit its overexploitation. Keywords: Prunus africana, community forests, multiple uses, traditional medicine, sustainable management, DR Congo